Value-Orientation Preferences of a Youth with Different Level of Financial Security - Vasyutinsky, Vadim Aleksandrovich (Psychological Prospects Journal, 2012)
According to the results of polling 2100 inhabitants of 6 cities of Ukraine, it was discovered that the young respondents were more clear oriented on the positive emotional experiences, interaction with the surroundings, and the active methods of social involvement. Strengthening the Ukrainian patriotism was linked with polarization of their language preferences. A financially secured youth had a higher life satisfaction, the more distinct civic orientations, and the more positive attitudes to education. The poor young people were less satisfied, had the weaker civic orientations, depreciated importance of education, and more favorably regarded the Ukrainian language.